دور المعرفة العلمية والمهنية المكتسبة في تنمية قدرات مراجعي الحسابات - الضويلة سعدون مفتاح; الفاخري بوبكر خالد; الكاديكي أحمد علي (Scientific Journal of University of Benghazi, 2022)
The current study aims to clarify the role of the scientific and professional knowledge acquired by auditors in developing their personal capabilities. To achieve the aim of the study, the questionnaire was distributed to the study sample and the statistical program (SPSS) was used to analyze the data. The study concluded that all components of scientific knowledge were available to the respondents of this study. The same is true with regard to professional knowledge, which is also very similar to the study sample. An auditor's experience is affected by the scientific and professional knowledge acquired by the auditor.